Identification of the critical microstructural parameters on the corrosion behaviour of commercially pure aluminium alloy. (November 2022) - Ingle, A.; Heurtault, S.; Hafid, F.; Said, J.; Proietti, A.; Odemer, G.; Dehmas, M.; Blanc, C.
Abstract: The influence of microstructure on the corrosion behaviour of commercially pure Al alloy in a chloride-containing sulphate solution was systematically investigated. An isothermal annealing at 300 °C led to an increase in the density of high-angle grain boundaries (HAGBs) and decrease in number density of intermetallic particles (IMPs). The grain size did not affect the pitting potential, but the corrosion current decreased with increase in the density of HAGBs. IMPs acted as pit initiation sites and influenced the pitting potential. After pit initiation, pit propagation occurred along HAGBs; pit width and depth were strongly dependent on the density of HAGBs. Graphical Abstract: ga1 Highlights: Model microstructures were designed for commercially pure Al alloy (CPAA). Increase in HAGB density and dissolution of precipitates after annealing at 300 °C. An increase in HAGB density led to a decrease in the corrosion current density. Fe-rich particles were the main microstructural parameter for pit initiation. Pit propagation was promoted by an increase in the density of HAGBs.